Developing a Teacher Module on the Application of Unplugged Coding in Handwashing Skills Learning for Children with Down Syndrome - Wulandari Eni; Chamidah Atien Nur (Universitas Negeri Padang, 2026)
This study aims to develop a teacher module on the application of unplugged coding (coding without a computer) in learning handwashing skills for children with Down syndrome. This study also aims to test the feasibility of the module based on the assessment of material experts and media experts, as well as to test the Pub. effectiveness of the module in improving teacher competency. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) The resulting product is a Google Sites-based digital module called “SI TEPAT”. The validation results show that this module is